Obstructive sleep apnoea is related to melanoma aggressiveness through paraspeckle protein-1 upregulation. Issue 2 (2nd February 2023) - Cubillos-Zapata, Carolina; Martínez-García, Miguel Ángel; Díaz-García, Elena; García-Tovar, Sara; Campos-Rodríguez, Francisco; Sánchez-de-la-Torre, Manuel; Nagore, Eduardo; Martorell-Calatayud, Antonio; Blasco, Luis Hernández; Pastor, Esther; Abad-Capa, Jorge; Montserrat, Josep María; et al.
Background: In patients with obstructive sleep apnoea (OSA), intermittent hypoxia induces overexpression of paraspeckle component (PSPC)1, a master modulator of transforming growth factor (TGF)-β signalling, which promotes cell cancer progression through epithelial–mesenchymal transition (EMT) and acquisition of cancer stem cell (CSC)-like features. However, the persistence of intermittent hypoxia-induced effects on PSPC1, and their consequences in cancer patients are not known. To this effect, circulating PSPC1 levels were compared in patients with cutaneous melanoma with or without OSA, and their relationship with tumour aggressiveness along with the in vitro effects of soluble PSPC1 and intermittent hypoxia on melanoma cell aggressiveness mechanisms were assessed. Methods: In 292 cutaneous melanoma patients, sleep studies and serum levels of PSPC1 and TGF-β were evaluated. The effect of PSPC1 on expression of EMT and CSC transcription factors was assessed using melanoma cell lines with patient sera under both normoxia and intermittent hypoxia conditions. Results: PSPC1 levels were higher in patients with moderate–severe OSA compared with mild OSA or non-OSA patients. Serum levels of PSPC1 were associated with several cutaneous melanoma clinical aggressiveness indicators. Both intermittent hypoxia exposures and serum from OSA patients upregulated TGF-β expression and amplified the expression of transcription factors associated with EMT activation and acquisition of CSC characteristics. Conclusion: In cutaneous melanoma patients, OSA severity is associated with higher PSPC1 serum levels, which jointly with intermittent hypoxia would enhance the self-reprogramming capabilities of EMT and CSC feature acquisition of melanoma cells, promoting their intrinsic aggressiveness. In melanoma patients, sleep apnoea promotes the self-reprogramming capabilities of epithelial–mesenchymal transition and cancer stem cell-like features acquisition in tumour cells, increasing their intrinsic aggressiveness https://bit.ly/3eA2oxm